(RE)MAKING DIGITAL IMAGINARIES WITH VIDEOGAME DEVELOPMENT: DO-IT-YOURSELF (DIY) DISRUPTIONS TO SOCIAL INEQUITY - Dahya, Negin; Jenson, Jennifer (AoIR Selected Papers of Internet Research, 2015)
Digital media has altered not only the form through which we communicate, but also the type of both communication and learning that transpires across transmedia platforms. ‘Do-it-yourself’ (DIY) productions reflect changing forms of communication, education and civic engagement (Ratto & Boler, 2014; Stack & Kelly, 2006) and represent new possibilities for not only imagining social interactions and opportunities, but also constructing them. In this paper, we draw on Charles Taylor’s (2005) definition of ‘social imaginaries’ to consider “the ways people imagine their social existence” (p. 23) in the context of digital industries and maker spaces. Networked digital technologies in particular enhance the possibility of sharing and collaborating across geographical and conceptual social divides. In recent years there has been growing recognition that digital media like film and videogames can create opportunities to interrupt social norms – to ‘show what you know’ to, with, at and across boundaries. Importantly, multimedia production creates a process of reflective (re)making that incorporates knowledge and experience from varied aspects of an individuals life into a product that can be reviewed, remixed, and reflected upon later on (Pink, 2001, 2007). This process of working with and creating digital artifacts informs and transforms society, creating an opportunity – a new imaginary – for continual dialogue and altered networks and social norms, circulating around digital artifacts throughout production and after.